Functional Connectivity Changes in Obsessive–Compulsive Disorder Correspond to Interference Control and Obsessions Severity - Fajnerova, Iveta; Gregus, David; Francova, Anna; Noskova, Eliska; Koprivova, Jana; Stopkova, Pavla; Hlinka, Jaroslav; Horacek, Jiri (Frontiers in Neurology, 2020)
Introduction: Deficit in neurocognitive mechanisms such as inhibition control and cognitive flexibility have been suggested to mediate the symptoms in obsessive-compulsive disorder (OCD). These mechanisms are proposedly controlled by the ‘affective’ and ‘executive’ orbitofronto-striato-thalamo-cortical (CSTC) circuits with well documented morphological and functional alterations in OCD that are associated with OCD symptoms. The precuneus region has been suggested in OCD as another key structure associated with the mechanism of ‘thought-action fusion’. Our study aimed to elucidate the association of the altered functional coupling of the CSTCs nodes (and precuneus), the OCD symptoms and interference control/cognitive flexibility. Methods: In a group of 36 (17 medicated and 19 drug-free) OCD patients and matched healthy volunteers, we tested functional connectivity (FC) within the constituents of the dorsolateral prefrontal cortex ‘executive’ CSTC, and the orbitofrontal cortex/anterior cingulate ‘affective’ CSTC, and precuneus. The functional connections showing the strongest effects were subsequently entered as explanatory variables to multiple regression analyses to identify possible associations between observed alterations of functional coupling and cognitive (Stroop test) and clinical measures (obsessions, compulsions and anxiety level). Results: We observed increased FC (FWE p<0.05 corr.) between CSTC seeds and regions of the parieto-occipital cortex, and between the precuneus and the angular gyrus and dorsolateral prefrontal cortex. Decreased FC was observed within the CSTC loop (caudate nucleus and thalamus) and between the anterior cingulate cortex and the limbic lobe. Linear regression identified a relationship between the altered functional coupling of thalamus with the right somatomotor parietal cortex and the Stroop color-words score. Similar association of thalamus FC has been identified also for obsessions severity. No association was observed for compulsions and anxiety. Conclusions: Our findings demonstrate altered FC in OCD patients with a prevailing increase in FC originating in CSTC regions towards other cortical areas, and a decrease in FC within the constituents of CSTC loops. Moreover, our results support the role of precuneus in OCD. The association of the cognitive and clinical symptoms with the FC between the thalamus and somatomotor cortex indicates that cognitive flexibility and inhibitory control are strongly linked and both mechanisms might contribute to the symptomatology of OCD.